Wellbeing and chronic lung disease incidence: The Survey of Health, Ageing and Retirement in Europe. - Judith A Okely; Seif O Shaheen; Alexander Weiss; Catharine R Gale (PLoS ONE)
Background Previous studies indicate that psychosocial factors can impact COPD prevalence. However, research into this association has predominantly focused on negative factors such as depression. The aim of this study was to examine whether high subjective wellbeing is associated with a lower risk of developing COPD. Methods The sample consisted of 12,246 participants aged ≥50 years from the Survey of Health, Ageing and Retirement in Europe. We used Cox proportional hazards regression to examine the relationship between wellbeing (measured using the CASP-12) and incidence of COPD over a follow-up period of 9 years. Results There was a significant association between wellbeing and COPD risk. In age-adjusted analyses, a standard deviation increase in CASP-12 score was associated with a reduced risk of COPD; hazard ratios (95% confidence intervals) for men and women were 0.67 (0.60-0.75) and 0.80 (0.73-0.87) respectively. After additional adjustment for demographic and health behaviour variables, this association remained significant for men but not for women: the fully-adjusted hazard ratios were 0.80 (0.70-0.91) and 0.91 (0.82-1.03) respectively. Conclusions Greater wellbeing is associated with a reduced risk of COPD, particularly in men. Future research is needed to establish whether gender reliably moderates this association.